Optimal estimation of the surface fluxes of methyl chloride using a 3-D global chemical transport model - X. Xiao (Atmospheric Chemistry and Physics, 2010)
Methyl chloride (CH3Cl) is a chlorine-containing trace gas in the atmosphere contributing significantly to stratospheric ozone depletion. Large uncertainties in estimates of its source and sink magnitudes and temporal and spatial variations currently exist. GEIA inventories and other bottom-up emission estimates are used to construct a priori maps of the surface fluxes of CH3Cl. The Model of Atmospheric Transport and Chemistry (MATCH), driven by NCEP interannually varying meteorological data, is then used to simulate CH3Cl mole fractions and quantify the time series of sensitivities of the mole fractions at each measurement site to the surface fluxes of various regional and global sources and sinks. We then implement the Kalman filter (with the unit pulse response method) to estimate the surface fluxes on regional/global scales with monthly resolution from January 2000 to December 2004. High frequency observations from the AGAGE, SOGE, NIES, and NOAA/ESRL HATS in situ networks and low frequency observations from the NOAA/ESRL HATS flask network are used to constrain the source and sink magnitudes. The inversion results indicate global total emissions around 4100 ± 470 Gg yr−1 with very large emissions of 2200 ± 390 Gg yr−1 from tropical plants, which turn out to be the largest single source in the CH3Cl budget. Relative to their a priori annual estimates, the inversion increases global annual fungal and tropical emissions, and reduces the global oceanic source. The inversion implies greater seasonal and interannual oscillations of the natural sources and sink of CH3Cl compared to the a priori. The inversion also reflects the strong effects of the 2002/2003 globally widespread heat waves and droughts on global emissions from tropical plants, biomass burning and salt marshes, and on the soil sink.